Efficient degradation of bisphenol A using High-Frequency Ultrasound: Analysis of influencing factors and mechanistic investigation. (20th September 2019) - Meng, Liang; Gan, Lu; Gong, Han; Su, Jun; Wang, Ping; Li, Wei; Chu, Wei; Xu, Lijie
Abstract: The environmentally friendly technology of high-frequency ultrasonic processes with the mostly concerned frequencies of 200 kHz and 400 kHz were applied and investigated systematically for BPA degradation in both pure water and river water mediated conditions. Investigations were carried out examining the effects of crucial parameters determining the system efficiency and BPA degradation mechanisms. Results proved that BPA was efficiently degraded via the oxidation by OH. The 400 kHz ultrasonic process demonstrated much stronger capability in generating OH and corresponding higher efficiency in BPA degradation based on electron spin resonance analysis. Increasing solution volume could increase the radical yields, and the temperature increase rate (dT/dt) showed linear relationship with k obs . In addition, the degradation of BPA with different concentrations was for the first time found controlled by different limiting factors, in which the degradation only with higher concentrations (≥0.02 mM) conformed to the Langmuir–Hinshelwood mechanism. More acidic condition and the bulk temperature of about 40 °C favored BPA degradation. The presence of NO3 −, SO4 2−, and Cl − demonstrated minor influence while CO3 2−, HCO3 − and NO2 − showed significant inhibition, and the effects of different anions also depended on their concentrations. The degradation rate decreased 23% when river water was used as the matrix. Furthermore, both hydroxylation of the benzene ring and attack on the connecting carbon were found to be the reaction pathways, and the latter was proposed to be more dominant. Graphical abstract: Image 1 Highlights: BPA degradation using High-Frequency Ultrasound was efficient even in river water. BPA degradation conformed to the L-H mechanism only at higher concentrations. Cleavage of the C–C bond connecting two phenyl groups was the dominant pathway. Effects of different anions depended on both the species and their concentrations. The initial temperature increase was an indicator of the process efficiency.